2017
DOI: 10.1080/21645515.2016.1255834
|View full text |Cite
|
Sign up to set email alerts
|

Injecting rabies immunoglobulin (RIG) into wounds only: A significant saving of lives and costly RIG

Abstract: An increasing number of dog bite victims were being presented to public hospitals in Himachal Pradesh in 2014 amidst virtual non availability of any rabies immunoglobulin (RIG). Only a small quantity of equine rabies immunoglobulin (eRIG) was available from the government owned Central Research Institute (CRI) Kasauli. This available eRIG was used in 269 patients as an emergency response and only for local infiltration of severe bite wounds by suspected rabid dogs. This was followed by rabies vaccination, usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 11 publications
(30 reference statements)
0
37
0
Order By: Relevance
“…Administration of rabies IG into and around the wound is critical to maximize effectiveness, and treatment failures have been previously reported when rabies IG was not appropriately infiltrated into wounds. [31][32][33][34] A study of 192 patients who received 40 IU/kg of equine rabies IG with confirmed infiltration into and around the wound reported that 39% (N = 75) of patients received full infiltration at the wound site, and 38% (N = 72) of patients received 50% or less of the rabies IG dose at the wound site. 35 Another study reported that a less than adequate volume of rabies IG was infiltrated into and around the wounds of 42% of patients who received postexposure prophylaxis in the emergency department in another region of the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of rabies IG into and around the wound is critical to maximize effectiveness, and treatment failures have been previously reported when rabies IG was not appropriately infiltrated into wounds. [31][32][33][34] A study of 192 patients who received 40 IU/kg of equine rabies IG with confirmed infiltration into and around the wound reported that 39% (N = 75) of patients received full infiltration at the wound site, and 38% (N = 72) of patients received 50% or less of the rabies IG dose at the wound site. 35 Another study reported that a less than adequate volume of rabies IG was infiltrated into and around the wounds of 42% of patients who received postexposure prophylaxis in the emergency department in another region of the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Due to limited RIG availability, patients (N = 700, median age: 30 years, median weight: 53 kg, sex ratio: 63:37 male:female) were administered RIG under a dose-sparing approach of infiltration of the wound only. All survived on follow-up [8,9]. We used bootstrap sampling of these data, where patient weight was measured, to capture variability in RIG use under two scenarios: (1) infiltration at the wound (s) with the remainder administered intramuscularly distant from the wound; and (2) infiltration of the wound(s) only.…”
Section: Rig Deliverymentioning
confidence: 99%
“…The overall cost of this scenario is the sum of costs for PrEP, PEP for pre-vaccinated children and PEP for unvaccinated children and adults. Cumulative costs were discounted at a rate of 0.04 [8] and DALYs averted were based on a 19% risk of developing rabies after exposure by a suspect rabid animal [21].…”
Section: B N'djamena Chadmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, the dose of RIG was based on the anatomical localisation of the affected area instead of the body weight of the individual [10]. Maximum infiltration of RIG into and around the wound is effective but the benefit from additional IM administration of any remaining RIG based on a person's body weight at a site distant to the wound may be limited [2,11,12]. The amount of administered RIG is therefore in almost all cases based on the size of the wound.…”
Section: Introductionmentioning
confidence: 99%